SOIL ORGANIC MATTER DYNAMICS UPON SECONDARY SUCCESSION IN IMPERATA GRASSLAND, EAST KALIMANTAN, INDONESIA - Yassir, Ishak; Buurman, Peter (Indonesian Journal of Forestry Research, 2015)
Soil organic matter (SOM) dynamics upon secondary succession in Imperata grassland was studied by stable carbon isotope analysis. The data of litter and soil samples of twenty plots in four different stages of successions were compared. These different stages were represented by plots that were; (1) burnt 3 years before sampling/observation (Imperata grassland), (2) burnt 9 years before sampling /observation, (3) secondary forest (â¥15 years) and (4) primary forest. The results showed that isotopic signatures of all soil horizons of the regeneration stages were statistically different from those of the primary forest. The A-horizon under the 3-years Imperata plot still contained 23% forest (C3) carbon, and this fraction increased to 51% in the-B-horizon. In the 9-years plot and in the secondary forest, the C3 carbon in the A-horizon increased to 51% and 96%, respectively.Â  In the topsoil, the loss of C4-C between the 3-years and the 9-years plot was significant, while it appeared negligible in the AB-horizon. The strong decay in the topsoil under Imperata grassland may be due to the rather high carbohydrate content of the SOM, which is considered easily decomposable. Further research is needed especially to explore the relation between carbon stocks and chemical composition of SOM. Such insight may help to better understand and predict soil carbon changes in relation to climate and vegetation change.